Inverted neutrino mass hierarchy and mixing in the Zee-Babu model - Vien, Vo Van; Long, Hoang Ngoc; Thu, Phan Ngoc (Communications in Physics, 2016)
We show that the neutrino mass matrix of the Zee-Babu model isable to fit the recent data on neutrino masses and mixingwith non-zero θ_13 in the inverted neutrino mass hierarchy. The results show that the Majorana phases are equal to zero and the Dirac phase () ispredicted to either 0 or π, i. e, there is no CP violation in the Zee-Babu model at the two loop level. The effective mass governingneutrinoless double beta decay and the sum of neutrino masses areconsistent with the recent analysis.